2009
DOI: 10.4209/aaqr.2008.12.0061
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PCDD/Fs in a Particles Filtration Device with Activated Carbon Injection

Abstract: Although numerous investigations have monitored polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofuran (PCDD/F) emissions from large municipal solid waste incinerators (MSWIs) and undertaken laboratory experiments to identify the formation mechanisms of PCDD/F, the PCDD/F profiles inside an air-pollution control device have seldom been determined. This study presents the outcome of a dioxin abatement program that injected particulate activated carbon (PAC) into an MSWI. The fly ashes collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…Data points of ambient air sites cluster first with those of MWI, and then with open burning (OB) and crematories (CM). Previous studies have shown that PCDD/F emissions from crematories, medical waste incinerators and joss paper (semi-open systems) did significantly affect the surrounding environment Wang et al, 2003c;Hu et al, 2009;Wang et al, 2009b). The above results indicate that the ambient air samples were influenced significantly by stationary emission sources (MWI, ALS, EAF and CM) and open burning (OB).…”
Section: Principal Components Analysis and Cluster Analysissupporting
confidence: 50%
“…Data points of ambient air sites cluster first with those of MWI, and then with open burning (OB) and crematories (CM). Previous studies have shown that PCDD/F emissions from crematories, medical waste incinerators and joss paper (semi-open systems) did significantly affect the surrounding environment Wang et al, 2003c;Hu et al, 2009;Wang et al, 2009b). The above results indicate that the ambient air samples were influenced significantly by stationary emission sources (MWI, ALS, EAF and CM) and open burning (OB).…”
Section: Principal Components Analysis and Cluster Analysissupporting
confidence: 50%
“…The predominant congeners are OCDD, followed by 1,2,3,4,6,7,1,2,3,4,6,7,, and OCDF. The congener profile of ambient air was different from stack flue gas from a municipal solid waste incinerator or from unburned joss paper, such as OCDD, HpCDF, HpCDD, HxCDF and HxCDD (Hu et al, 2009;Wang et al, 2009).…”
Section: Pcdd/fs In Tap Watermentioning
confidence: 99%
“…Considerable research has examined the reaction mechanisms of PCDD/Fs in the Waelz process, and the results indicate that PCDD/Fs are mainly formed by the de novo synthesis from carbon sources and inorganic chloride (Huang and Buekens, 1996;Buekens et al, 2001;Wang et al, 2009b;Lin et al, 2010b;Chen et al, 2011). However, the formation and transformation reactions of PCDD/Fs in the vitrification process, which do not need any auxiliary fuel, are still not well understood.…”
Section: Introductionmentioning
confidence: 99%